The Need of Endodontic Therapy among Patients Attending Tertiary Care Center in Central Nepal - Acharya, N.; Humagain, R.; Dahal, S.; Kafle, D. (Kathmandu University Medical Journal, 2022)
Background Dental caries is considered as the most prevalent oral disease in Nepalese population that frequently needs endodontic therapy or root canal treatment (RCT). Pulp infection is one of the most common sequels of dental caries which when left untreated leads to pulpal necrosis and peri-radicular diseases. Patients usually reports to the dental hospital after there is pain, sensitivity, swelling or fracture of the tooth structure which usually impedes their normal routine of daily life. RCT is one of the efficacious therapeutic procedures that can save the teeth retaining its aesthetics and function. Objective To determine the need of RCT among patients attending Tertiary Care Hospital. Method A cross-sectional epidemiological study was conducted in the Department of Conservative Dentistry and Endodontics over the period of one year from April 2019 to April 2020. Ethical approval was taken from the Institutional Review Committee Kathmandu University School of Medical Sciences. In total, 7566 records of the patients that needed endodontic therapy and other treatments were collected and the need of endodontic therapy versus other treatments were assessed. The data obtained were analyzed using the SPSS version 20. The association between various patient-related variables were calculated by chi square test and mean, standard deviation, frequency and percentage were calculated using descriptive statistics. P value was set at < 0.05 for statistical significance. Result Among the total study population, (n=7566), the mean age was 34.97±14.34 years among which 4387 (58%) were females and 3179 (42%) were males. The type of treatment required by the study participants were significantly associated with age and sex (p < 0.001) and p < 0.001, respectively). Conclusion The findings of this study concluded that there was an increased need for endodontic therapy among patients visiting the department compared to other treatments. There was a significant association between gender and age showing females and elderly patients in greater need for endodontic therapy.